Unanswerable Questions About Images and Texts - Davis, Ernest (Frontiers in Artificial Intelligence, 2020)
Questions about a text or an image that cannot be answered raise distinctive issues for an AI. This note discusses the problem of unanswerable questions in VQA (visual question answering), in QA (visual question answering), and in AI generally.